Prognostic value of coronary computed tomography angiographic derived fractional flow reserve: a systematic review and meta-analysis - Nørgaard, Bjarne L; Gaur, Sara; Fairbairn, Timothy A; Douglas, Pam S; Jensen, Jesper M; Patel, Manesh R; Ihdayhid, Abdul R; Ko, Brian S H; Sellers, Stephanie L; Weir-McCall, Jonathan; Matsuo, Hitoshi; Sand, Niels Peter R; et al. (Heart (British Cardiac Society), 2022)
ObjectivesTo obtain more powerful assessment of the prognostic value of fractional flow reserveCT testing we performed a systematic literature review and collaborative meta-analysis of studies that assessed clinical outcomes of CT-derived calculation of FFR (FFRCT) (HeartFlow) analysis in patients with stable coronary artery disease (CAD).MethodsWe searched PubMed and Web of Science electronic databases for published studies that evaluated clinical outcomes following fractional flow reserveCT testing between 1 January 2010 and 31 December 2020. The primary endpoint was defined as ‘all-cause mortality (ACM) or myocardial infarction (MI)’ at 12-month follow-up. Exploratory analyses were performed using major adverse cardiovascular events (MACEs, ACM+MI+unplanned revascularisation), ACM, MI, spontaneous MI or unplanned (>3 months) revascularisation as the endpoint.ResultsFive studies were identified including a total of 5460 patients eligible for meta-analyses. The primary endpoint occurred in 60 (1.1%) patients, 0.6% (13/2126) with FFRCT>0.80% and 1.4% (47/3334) with FFRCT ≤0.80 (relative risk (RR) 2.31 (95% CI 1.29 to 4.13), p=0.005). Likewise, MACE, MI, spontaneous MI or unplanned revascularisation occurred more frequently in patients with FFRCT ≤0.80 versus patients with FFRCT >0.80. Each 0.10-unit FFRCT reduction was associated with a greater risk of the primary endpoint (RR 1.67 (95% CI 1.47 to 1.87), p<0.001).ConclusionsThe 12-month outcomes in patients with stable CAD show low rates of events in those with a negative FFRCT result, and lower risk of an unfavourable outcome in patients with a negative test result compared with patients with a positive test result. Moreover, the FFRCT numerical value was inversely associated with outcomes.